Role of phenolic compounds from brazilian native fruits on obesity-induced insulin resistance in skeletal muscle - Pessoa, Erika Vicencia Monteiro (2021)
Skeletal muscle is an important metabolic tissue in glucose uptake and thus in glycemic homeostasis. Evidence suggests that phenolic compounds may exert beneficial health effects against metabolic disorders associated to obesity including its state of peripheral insulin resistance. The objective of this work was to investigate the role of phenolic compounds present in two Brazilian native fruits, cambuci (Campomanesia phaea Berg.) and jaboticaba (Plinia jaboticaba (Vell.) Berg), on the insulin resistance in the skeletal muscle of obese mice fed a high-fat-sucrose diet (HFS). For this, two independent experimental protocols were used for each fruit, where male C57BL/6J mice fed the HFS diet for the induction to obesity were used. Once the condition of obesity was established, animals started to receive daily oral administration (by gavage) of extracts enriched in phenolic compounds obtained from each fruit, in doses reachable through the diet. At the end of the experiments, the animals were euthanized and their tissue and organs collected. The animals receiving extracts of jaboticaba and cambuci, regardless of the dose, presented lower body weight gain in relation to the HFS group. The results for weekly fasting glycemia and glucose tolerance of the animals that received the phenolic extracts of both fruits showed an improvement in glycemic homeostasis even when fed with the deleterious diet. In the gastrocnemius muscle of the animals was demonstrated that cambuci and jaboticaba extracts significantly increased the content of glucose transporter protein 4 (GLUT-4) and AMPactivated protein kinase (AMPK-Thr172), which has a broad role in metabolic regulation. Regarding inflammation, the administration of extracts from both fruits favored the reduction of phosphorylation and activation of the nuclear factor-κe (NF-κB) and the expression of some genes such as IL-6, TNF-α, IL-1β, and JNK, whose increase has been associated with insulin resistance. In conclusion, this study suggests that the phenolics present in both native fruits may be important therapeutic agents in the reduction of muscle insulin resistance and inflammation associated with obesity.